The HBG2 rs7482144 (C > T) Polymorphism is Linked to HbF Levels but not to the Severity of Sickle Cell Anemia - Lakkakula, Bhaskar V. K. S.; Pattnaik, Smaranika (Journal of Pediatric Genetics, 2021)
Sickle cell anemia (SCA) is a severe disease characterized by anemia, acute clinical complications, and a relatively short life span. In this disease, abnormal hemoglobin makes the red blood cells deformed, rigid, and sticky. Fetal hemoglobin (HbF) is one of the key modulators of SCA morbidity and mortality. Interindividual HbF variation is a heritable trait that is controlled by polymorphism in genes linked and unlinked to the hemoglobin β gene (HBB). The genetic polymorphisms that determine HbF levels are known to ameliorate acute clinical events. About 190 well-characterized homozygous SCA patients were included in this study. Complete blood count (CBC), high-performance liquid chromatography (HPLC), and clinical investigations were obtained from patient's records. Severity scores were determined by using the combination of anemia, complications, total leucocyte count, and transfusion scores. HBG2 rs7482144 polymorphism was genotyped by using the polymerase chain reaction and restriction fragment length polymorphism. The association between HBG2 rs7482144 polymorphism and HbF levels as well as the disease severity of SCA were assessed. SCA patients carrying TT genotype were found to have higher HbF levels. In addition, SCA patients with increased severity showed significantly lower levels of hemoglobin, HbF, and hematocrit values. However, the genotypes of HBG2 rs7482144 polymorphism were not found to be associated with the risk of disease severity. In summary, this study demonstrated that HBG2 rs7482144 polymorphism is linked with HbF levels, but it does not affect disease severity. The sample sizes used and the pattern of association deduced from our small sample size prevents us from extrapolating our findings further.
Keywords: sickle cell anemia; HBG2 rs7482144 polymorphism; fetal hemoglobin; severity scores